Effects of Online Cooperative Learning on Students’ Problem-Solving Ability and Learning Satisfaction - Wang, Yi-Ping; Wu, Tung-Ju (Frontiers in Psychology, 2022)
Along with changing technologies, students do not simply acquire knowledge from teachers. In face of diverse student background, teachers have to make adjustment in the instruction so that students do not simply listen. Student-based educational philosophy means to promote each student that instructional methods with cooperative learning allow students changing from passive learning to active knowledge construction, reinduce students’ learning motivation and passion, and enhance students’ self-learning effectiveness. Aiming at college students in Fujian Province as the research samples, total 360 copies of questionnaire are distributed for this study. After deducting invalid and incomplete ones, 298 copies are valid, with the retrieval rate 83%. The research results show significantly positive correlations between 1. information technology integrated online cooperative learning and problem-solving ability, 2. problem-solving ability and learning satisfaction, as well as 3. information technology integrated online cooperative learning and learning satisfaction. According to the results to proposed discussions, it is expected, in the digital era, to integrate information technology into teaching environment and focus on learning objectives to have teaching software present user-friendly interface, simple operation, learning process recording, and interactive learning community in the teaching-learning process to develop the characteristics and effectiveness of digital teaching and learning.